Structural Characterization of Metal free Organic Dyes Sensitized Solar Cell(Dssc)theory for Harvesting System: - (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Density functional theory (DFT) and time-dependent density functional theory (TD-DFT)calculations were carried out to ascertain whether or not certain new metal-free 1,3,4-oxadiazolecompounds O1-O7 may serve as metal-free organic dyes in the application of dye-sensitized solar cells(DSSCs). The relative efficiency of the compounds as dyes in DSSCs were determined by analyzing theirelectron contributions, hole contributions, and electron-hole overlaps, with an emphasis on the electrondensities on the anchoring segments. The charge separation distance (r) and the electron-hole overlap ()were studied because excitations cause charge transfer (CT), and because transition density matrices(TDM) describe the separation of each electron from its corresponding hole. Electron excitationprocesses may be described by a number of parameters such as the diffusion constant (D) and theelectron lifetime (t). Since O3 had the highest IPCE value, it was deemed to be the most efficient dye.